QUALITATIVE ANALYSIS OF PORKCINE CONTENT ON NUGGET AND MEATBALLS CIRCULATING IN THE CITY OF MAMUJU - tikirik, wita oyleri (Journal of International Multidisciplinary Research, 2023)
Halal food means food that is permitted under Islamic law and meets the requirements, namely that it does not contain any ingredients that are not permitted under Islamic law. The absence of information regarding the halal food contained in food sold in Mamuju City means that it is necessary to carry out research that can provide information regarding the halalness of food products sold by traders in Mamuju City, especially instant food or ready-to-eat food that does not have a halal brand, logo or permit. BPOM (Food and Drug Supervisory Agency). This research aims to detect pork contamination in unbranded nuggets and meatballs sold by producers and traders in Mamuju. The method used was to carry out tests using a Porkcine detection kit on unbranded nugget and meatball food samples. The positive control used was a sample of processed meat containing pork. The test results showed that all food samples of nuggets (3 types) and meatballs (3 types) did not contain pork protein (negative results). This way the food is safe for consumption. This way the food is safe for consumption. Even though in this study the food tested negative contained non-halal food ingredients, consumers should still be careful in choosing the food they want to consume, especially products that do not have the product name, list of ingredients used, net weight or net content, name and address of the party. Who produces or imports, halal for those required, production date and code, expiration information, distribution permit number, and the origin of certain food ingredients